Injection Characteristics Study of High Pressure Direct Injector for Compressed Natural Gas (CNG) using Experimental and Analytical Method - Zahari, Taha; Mohd Fadzil, Abdul Rahim; R., Mamat (The Institute of Physics, 2017)
Utilization of compressed natural gas in transportation is driven by factors such as stringent emission level its competitive price. The characteristics of injector used to deliver compressed natural gas (CNG) are critical to the success of direct injection spark ignition engine application. The injection characteristics affect mostly the mixture formation and combustion processes. Thus measurement of injector flow rate which is used in high pressure direct injection compressed natural gas engine (HPDI-CNG) is carried out in two cases were done. The first case investigated the effect of CNG injection pressure and the second case evaluate the effect of pulsewidth of injection duration on injector mass flow rate. An analytical model was developed to investigate the relationship between the injection parameter which ultimately affect the mass flow rate of the injector. The injector was operated in choked condition in both the experiments and simulation studies. The selected pressure ratios used in the study exceeded the critical pressure ratio for the gas. In case 1, it was shown that mass flow rate through the injector is affected by injection pressure linearly. In case 2, it was also shown that average mass flow rate at short injection durations which are commonly used in engine maps is lower than recorded in Case 1. The injector model able to predict the trend of mass flow rate at different injection pressure and injection duration with justified discrepancy.